2021
DOI: 10.1002/solr.202100676
|View full text |Cite
|
Sign up to set email alerts
|

Vapor‐Transport‐Deposited Orthorhombic‐SnSe Thin Films: A Potential Cost‐Effective Absorber Material for Solar‐Cell Applications

Abstract: The power‐conversion efficiencies of orthorhombic tin selenide (α‐SnSe)‐based thin‐film solar cells (TFSCs) are very low—less than 1% in most cases—due to the poor crystallinity, small grains, and large number of defects. Herein, the highest cell efficiency of 2.51% together with a high short‐circuit current density of 28.07 mA cm−2 for α‐SnSe TFSCs grown via vapor‐transport‐deposition (VTD) is reported. The grain size and surface roughness of the SnSe thin films greatly influence the shunt properties of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…14 More recently, we used a similar approach to synthesize an orthorhombic SnSe absorber layer by means of VTD and achieved the highest cell efficiency of ∼2.5%. 15 Our results revealed that the SnS-based devices have a higher open-circuit voltage (V oc ), while the SnSe-based devices have a higher short-circuit current density (J sc ). The high V oc of SnS-based devices can be attributed to their relatively wide optical band gap and superior shunt properties.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…14 More recently, we used a similar approach to synthesize an orthorhombic SnSe absorber layer by means of VTD and achieved the highest cell efficiency of ∼2.5%. 15 Our results revealed that the SnS-based devices have a higher open-circuit voltage (V oc ), while the SnSe-based devices have a higher short-circuit current density (J sc ). The high V oc of SnS-based devices can be attributed to their relatively wide optical band gap and superior shunt properties.…”
Section: Introductionmentioning
confidence: 72%
“…These observed Raman peaks agree with the previous reports. 15,29,30 The peaks of SnS x Se 1−x are shifted between SnS and SnSe; however, no peak shift trend was observed. Prominently, the strong observable peak of secondary phases was not detected from the Raman analysis.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…52 SnSe devices based on VTD-deposited absorber layers have also been recently explored, yielding 2.5% PCE. 53 Notably, selenium (∼0.05 ppm) is less abundant in the earth’s crust than sulfur (∼420 ppm), 12 which points to the fact that these Se-based materials are perhaps less likely to be compatible with multiple TW-scale deployment.…”
Section: Emerging Thin-film Photovoltaics Contendersmentioning
confidence: 99%